Effects of two-stage harvesting soil loosening mechanism rotary tillage blade on Fritillaria ussuriensis Maxim collision damage - Song, Jiang; Wang, Yaoshen; Han, Yiyong; Ma, Bo; Bian, Jingyang; Wang, Sibo; Tian, Shuai (International Journal of Agricultural and Biological Engineering, 2025)
A two-stage harvester is one method for achieving high-efficiency and low-loss mechanized harvesting of Fritillaria ussuriensis Maxim (FUM), a perennial herb. To address the poor performance of the soil breaking mechanism, the soil breaking performance can be improved by adding a rotary tillage blade set based on the existing soil breaking mechanism; however, it easily causes damage to the FUM. Therefore, in this study, a numerical simulation method was used to obtain the minimum FUM energy loss and minimum damage when the width of the rotary tillage blade cutter edge was 8 mm. A FUM rotary-tillage blade collision damage test bed was built, and the influence of the rotational speed, cutter edge width, and collision direction on the FUM mass loss ratio was analyzed using a random block test. The results of the random block test showed that the influencing factor model of the FUM mass loss ratio was significant. The rotational speed and width had a significant influence on the mass loss ratio, and the collision direction only had a significant influence on the free FUM. The results of the single-factor test showed that the mass loss ratio was proportional to the rotational speed, and that it increased as the rotational speed increased. The order of influence of the collision direction on the mass loss ratio was Y>X>Z. The variation in the mass loss ratio and cutter edge width indicated that the mass loss ratio of the 8 mm-wide cutter edge was the smallest. The minimum damage caused by the 8 mm-wide cutter edge was also determined. The results of this study can provide a theoretical reference for the appropriate rotational speed of the low-loss soil-loosening mechanism in FUM topsoil stripping machines and the structural design of the rotary tillage blade. Key words: Fritillaria ussuriensisMaxim; two-stage harvester; soil-loosening mechanism; low-loss DOI: 10.25165/j.ijabe.20251806.8990 Citation: Song J, Wang Y S, Han Y Y, Ma B, Bian J Y, Wang S B, et al. Effects of two-stage harvesting soil loosening mechanism rotary tillage blade on Fritillaria ussuriensis Maxim collision damage. Int J Agric & Biol Eng, 2025; 18(6): 83–93.